2013
DOI: 10.1002/pola.26854
|View full text |Cite
|
Sign up to set email alerts
|

A new thermo-responsive block copolymer with tunable upper critical solution temperature and lower critical solution temperature in the alcohol/water mixture

Abstract: The multi-thermo-responsive block copolymer of poly [2-(2-methoxyethoxy)ethyl methacrylate]-block-poly[N-(4vinylbenzyl)-N,N-diethylamine] (PMEO 2 MA-b-PVEA) displaying phase transition at both the lower critical solution temperature (LCST) and the upper critical solution temperature (UCST) in the alcohol/water mixture is synthesized by reversible additionfragmentation chain transfer polymerization. The poly[2-(2methoxyethoxy)ethyl methacrylate] (PMEO 2 MA) block exhibits the UCST phase transition in alcohol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 74 publications
1
34
0
Order By: Relevance
“…However, water was found to be a cononsolvent in the system with a water content higher than 15 wt% indicated by the appearance of an LCST transition as well as a decrease of the T CP when the water content is increased. [115] Scheme 8…”
Section: Poly(n-isopropylacrylamide)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, water was found to be a cononsolvent in the system with a water content higher than 15 wt% indicated by the appearance of an LCST transition as well as a decrease of the T CP when the water content is increased. [115] Scheme 8…”
Section: Poly(n-isopropylacrylamide)mentioning
confidence: 99%
“…[115] The T CP of PDEGMA 29 in isopropanol (2.0 wt %) decreases from 27.8 to 17.8 o C with the addition of only 1 wt% of water indicating a cosolvency effect. When the water content increased to 5 wt%, the polymer becomes completely soluble in either the ethanol/water or isopropanol/water solvent mixtures.…”
mentioning
confidence: 98%
“…It is well known that the desired LCST could be controlled by adjusting pH, sodium chloride in water, different solvents, and the monomer molar fraction. Plate et al studied the structures and properties of N ‐alkyl‐substituted polyacrylamides and revealed that the phase transition temperature is decreased with an increasing length of alkyl side chains.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that a full phase diagram is required in order to characterize a true LCST, the T cp or CST is often referred to instead, and represents the temperature at which macroscopic precipitation occurs at a given concentration and under the chosen experimental conditions 8. Tuning the CST of thermoresponsive polymers is key with regards to their application, and has been found to depend on chemical composition, molecular weight, architecture, block length, concentration, solution state morphology, and pH, amongst other factors 9–15…”
Section: Figurementioning
confidence: 99%